A retrospective study of persistence, adherence, and health economic outcomes of fixed-dose combination vs loose-dose combination of oral anti-diabetes drugs. (3rd March 2016) - Lokhandwala, Tasneem; Smith, Nancy; Sternhufvud, Catarina; Sörstadius, Elisabeth; Lee, Won Chan; Mukherjee, Jayanti
Abstract: Objective: To compare outcomes between patients with type 2 diabetes mellitus (T2DM) using fixed-dose combination (FDC) and loose-dose combination (LDC) products. Methods: This retrospective cohort study used MarketScan® Commercial and Medicare Supplemental data from January 1, 2009–December 31, 2013. The identified population included patients with T2DM and ≥1 additional oral anti-diabetic prescription (of the same regimen [FDC/LDC] as the index prescription) within 12 months following the fill date. Persistence (no ≥30-day gap) and adherence (medication possession ratio [MPR] ≥0.8) were assessed as primary end-points; secondary end-points included hypoglycemia, healthcare resource utilization, and costs. Results: Of 23, 361 patients identified, 12, 590 (53.9%) were on FDC therapy and 10, 771 (46.1%) were on LDC therapy. FDC patients had a significantly lower rate of non-persistence (67.9% vs 73.4%, p  < 0.0001) and a significantly higher rate of adherence to therapy (57.0% vs 50.7%, p  < 0.0001) when compared to LDC patients. Average time to non-persistence was significantly longer among FDC vs LDC patients (207.1 vs 186.3 days, p  < 0.0001). After adjusting for baseline characteristics, the odds of non-persistence were 21% lower with FDC vs LDC therapy (OR = 0.79, 95% CI = 0.74–0.85, p  < 0.0001), with a 28% higher odds of adherence (OR = 1.28, 95% CI = 1.20–1.36, p  < 0.0001). Differences in most secondary outcomes significantly favored FDC therapy, including total predicted monthly all-cause costs ($1008 vs $1053; p  = 0.006) and T2DM-related costs ($142 vs $155; p  < 0.001). Limitations: Cohort classification was based on prescription claims data. The lack of clinical data limits assessment of potential influencers of FDC vs LDC decisions, residual confounding was possible, and diabetes-related medical costs only captured claims with a primary diagnosis for diabetes. The results may not be generalizable to populations such as Medicaid. Conclusion: Management of T2DM using FDC therapies provides a compliance benefit relative to LDC therapies that may translate to reductions in healthcare utilization and costs.